Bioethanol Production from Microalgae - Lam, M.K. (Elsevier Inc., 2015)
In recent years, cultivating microalgae for biofuel production has sparked a new dimension in the renewable fuel industry. Microalgae are fast-growing microorganisms and can be grown in diverse water sources, such as freshwater, seawater, wastewater, and brackish water. Microalgae are also able to accumulate high carbohydrate content within their cells, which can be a prospective feedstock for bioethanol production. The carbohydrate synthesized by microalgae is usually in the form of starch (without lignin), which makes it much easier to be converted to simple reducing sugar compared to lignocellulosic biomass. This chapter reviews the potential of bioethanol production from microalgae biomass, including the selection of microalgae species and processing of the microalgae carbohydrate to bioethanol. Â© 2015 Elsevier Inc. All rights reserved.